Profil Berpikir Kreatif Siswa SMP dalam Menyelesaikan Masalah Matematika Kontekstual Berdasarkan Perbedaan Tipe Kepribadian Introvert dan Ekstrovert - Selvia Desi Ekayana; Didik Hermanto; Moh Affaf (JEMS: Jurnal Edukasi Matematika dan Sains, 2020)
This research is a qualitative descriptive study. The research subjects consisted of female students with introverted personality and female students with extrovert personality. The instruments used in this study consisted of a personality test instrument, interview guidelines, and problem solving tasks (TPM). Data collection was carried out by means of contextual problem solving task-based interviews. The data validity test was conducted by means of time triangulation. The data analysis used refers to the 3 flows of data analysis from Milles & Huberman, namely data reduction, data presentation and conclusion drawing. The results of this study can be concluded as follows. Introverted students mentioned all the information contained in the questions correctly in a halting voice, while extrovert students mentioned all the information contained in the questions correctly and smoothly. The two students solved the questions in two ways even though the methods used were routine procedures that were commonly used by students. In re-examining the results obtained, the two students matched the results obtained with the steps in one method with another method.